The influence of online learning platform models during the COVID-19 outbreak on college student satisfaction levels in Southeast Sulawesi - Sumarna N; Kansil Y.E; Hamid R (Universitas Muhammadiyah Surabaya, 2020)
Abstract. During the COVID-19 outbreak, we had to do physical distancing, so that alluniversities in Indonesia conducted online class programs. This research focuses on the segmentation of college student assessment in choosing online learning platforms and in the context of their satisfaction. An empirical survey was conducted on 295 college students who were taught using various online learning platforms through online surveys. The results showed the selection and use of learning platforms significantly influence the level of college student satisfaction. The use of online learning platforms with a combination of Zoom + Google Classroom + WhatsApp application (model 1) becomes a very dominant choice used by college students in online learning when compared to other models